Mild to moderate hypohydration reduces boys` high-intensity cycling performance in the heat - Wilk, B.; Meyer, F.; Bar-Or, O.; Timmons, B. W. (European Journal of Applied Physiology, 2014)
Purpose To evaluate the effect of 1 and 2 % hypohydration on high-intensity cycling performance of 10- to 12-year-old boys in the heat. Methods In a counterbalanced order, nine boys attended three sessions in which they cycled intermittently (6 × 10-min bouts at 40-45 % VO2max ) in a climate chamber. During each session, environmental conditions and water intake were individually adjusted to achieve a target hypohydration level of 0, 1 or 2 %, based on change in body weight (BW). Following 45 min of rest in thermoneutral conditions when the target hypohydration was maintained, each boy re-entered the climate chamber (35 °C and 50-55 % RH) to perform the cycling performance test at 90 % VO2max until exhaustion. Heart rate (HR) and rectal temperature (T re) were recorded continuously throughout each session. Total mechanical work (TMW) was taken as a measure of cycling performance. Results Actual hypohydration level at the start of the cycling performance test in each session was: 0.1 ± 0.0 %, 1.1 ± 0.1 % and 2.0 ± 0.1 %. With 2 % hypohydration, TMW (35.5 ± 6.8 kJ) was significantly (p < 0.05) lower than with 0 % hypohydration (49.3 ± 9.8 kJ). When expressed as a percentage of TMW with 0 % hypohydration, TMW was reduced by 15.5 and 23.3 % with 1 and 2 % hypohydration, respectively (p < 0.05 for both). At the start of the cycling performance test, HR was 13 and 15 bpm higher, and T re was 0.3 °C higher (p < 0.05 for all) with 1 and 2 % hypohydration, respectively, compared with 0 % hypohydration. Conclusion Mild (~1 %) to moderate (~2 %) hypohydration reduces high-intensity cycling performance of healthy young boys in the heat.